Management of Hepatic Granulomatous Tuberculosis After BCG Therapy for Bladder Cancer - Ayati, Mohsen (Urol Case Rep, 2017)
BCG therapy is used as a treatment in bladder cancer. Intravesical administration of Bacillus Calmette-Guérin is used as a treatment method in superficial bladder cancer. While it is commonly effective, some serious side effects may occur. We hereby report a 65-year-old man who developed granulomatous hepatitis as a complication following BCG therapy. He was treated successfully with antitubercular therapy and prednisolone.